IMPROVING STUDENTS’ WRITING SKILL THROUGH GRAPHIC ORGANIZER IN PROCESS WRITING - Zakky Yavani (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2018)
Abstract: Within a production of text like written text, a writer in fact conducts series of processes which are not simple and easy. Grammar, vocabulary and content are among the problems; however, problems actually occur begin from even deciding what to write and how the ideas should be arranged. Employing collaborative classroom action research (CAR) design in two cycles, three meetings of 100 minutes each, this study aims to improve the students’ writing skill using graphic organizer. 16 students of an English course in Malang, east Java participated in this study. To get the result, questionnaire, observation checklist, writing test and field notes are collected. Meanwhile, expected criteria of success were that all students achieved the minimum passing grade of 65, and 85% of them actively involved in the implementation of the graphic organizer strategy and perceive the implementation positively. The finding shows the implementation of graphic organizer strategy was successful to improve the students’ writing ability. All the students achieved the score at least 67 and 90% of them actively involved in the process of writing persuasive text, and positive perception existed.